Por uma clínica Ética em Espinosa: Uma investigação do corpo e das forças - Gonçalves, Tarini Suzan Maciel (2023)
The aim of this research is to map the concept of the body, the composition between bodies, and the role of ethics in Spinoza's philosophy to discuss how these concepts can function as tools for clinical practices. With the intention of questioning conventional approaches in psychology, which often adopt normative practices in the clinic, we turn to Spinoza's philosophy to oppose the Cartesian dualistic thinking. In our view, the latter contributes to the maintenance of normalization and categorization processes frequently employed in these practices. To achieve this goal, a theoretical study was initially conducted, primarily based on Deleuze's interpretations of Spinoza. Our intention is to replace conventional concepts with those we identify as more effective in promoting a healthy and active life. Based on these terms, we map the clinical practice through a field diary, seeking to elucidate how these concepts provide support in the relationship between the psychologist and the client during the clinical encounter. The method employed throughout the research process, encompassing both theoretical study and the field diary and clinical practice, is the cartography. Ethical clinical practice aims to enhance real desire and understand the dynamics of composition that shape our existence. The results obtained reveal the effectiveness of these Spinozist concepts in the dynamic between the psychologist and the client during the clinical encounter. The notion of the body provides a solid guide for understanding the individual, while the logic of composition between bodies expands the understanding of the interaction between nature and the world. This transformative understanding highlights the importance of recognizing and valuing our affective experiences as authentic guides towards understanding ourselves.